PENGGUNAAN INSTAGRAM SEBAGAI MEDIA KOMUNIKASI PEMASARAN PRODUK ORANGE BUTTON - Mira Hildayanti; Yulia Sariwaty (JURNAL PURNAMA BERAZAM, 2020)
The existence of social media applications in the moderen era has been used by many people as a means of doing business, in addition to showing existence. In its development, marketing communication is now not only done conventionally but also through digital media. Caused by a virus pandemic that spreads in all parts of the world including Indonesia. Social media is changing its benefits in addition to disseminating information and communication, but can also function as a marketing media, and one of them is social media services that can be done as marketing access, as example social media Instagram. Instagram is a social media that can be used as marketing in the digital age in expanding and increasing consumer reach. The purpose of this research is to find out how PT Pinisi Terbang Menari manage an Instagram account as a marketing communication medium for Orange Button products as one of the products of PT Pinisi Terbang Menari, to compare with the development of sales since the early 2020 beginning of the pandemic. This research has been carried out since the beginning of April 2020 until July 2020. This study uses a qualitative approach, which is descriptive research with all the elaboration of the data collected. The results of the research are the use of Instagram which is done on the Orange Button products by PT Pinisi Terbang Menari by observe the problem, and focusing the results from the managed. The results showed that since 2020, when the pandemic occurred, it had become an obstacle for PT Pinisi Terbang Menari in conventional product marketing, but the use of Instagram social media in digital marketing was done to keep Orange Button products running and could help the company continue to survive and develop.